PENDIDIKAN KETRAMPILAN HIDUP Telaah Filosofis atas Life Skill Curriculum - Anita Lie (Studia Philosophica et Theologica, 2002)
What is life skill education? Why is its curriculum needed? How can life skill education be implemented into practical strategy of learning in our school? These are the fundamental questions that guide the developing thought of this article. To the extent of practical strategy that system of education should bring up students to be masters of their life, life skill education might be worth. Indonesia needs such a model of education. Yet, as one may guess easily, the mentality of Indonesian society is probably the huge challenge to cope when implementing this model. Life skill model of education needs a new perspective of “life”, not just that of “skill.” The article deals with philosophically some systems of life skill curriculum and its actual challenges. In order to transform such a model of education into an apt program in the context of Indonesia, we should be aware of the very close relationship between “being skillful” and “life context” in our system of education.